HTLV-1/2 seroprevalence and coinfection rate in Brazilian first-time blood donors: an 11-year follow-up - Pinto, Mariana Tomazini; Rodrigues, Evandra Strazza; Malta, Tathiane Maistro; Azevedo, Rochele; Takayanagui, Osvaldo Massaiti; Valente, Vanderléia Bárbaro; Ubiali, Eugênia Maria Amorim; Covas, Dimas Tadeu; Kashima, Simone (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
The seroprevalence and geographic distribution of HTLV-1/2 among blood donors are extremely important to transfusion services. We evaluated the seroprevalence of HTLV-1/2 infection among first-time blood donor candidates in Ribeirão Preto city and region. From January 2000 to December 2010, 1,038,489 blood donations were obtained and 301,470 were first-time blood donations. All samples were screened with serological tests for HTLV-1/2 using enzyme immunoassay (EIA). In addition, the frequency of coinfection with hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), Chagas disease (CD) and syphilis was also determined. In-house PCR was used as confirmatory test for HTLV-1/2. A total of 296 (0.1%) first-time donors were serologically reactive for HTLV-1/2. Confirmatory PCR of 63 samples showed that 28 were HTLV-1 positive, 13 HTLV-2 positive, 19 negative and three indeterminate. Regarding HTLV coinfection rates, the most prevalent was with HBV (51.3%) and HCV (35.9%), but coinfection with HIV, CD and syphilis was also detected. The real number of HTLV-infected individual and coinfection rate in the population is underestimated and epidemiological studies like ours are very informative.